Korean Soap Operas, Telenovelas and Sci-fi Conspiracies: A Game-making Experience with Latin American Youth in London - Paula, Bruno de (Digital Culture and Education, 2021)
This paper explores a game-making programme for 14 Latin American migrants aged 13-18 in London/UK, carried out between October/2017-January/2018, where I investigated the relationships between game conventions, platforms and personal preferences in the curation of fluid identities through game production. Participants presented varying levels of affinity with games linked both to access issues and to other specific elements (e.g. perception of games in contemporary culture, gender). Questionnaires, observations, unstructured/semistructured interviews and gaming archives were employed to explore this participatory initiative and data was analysed through Multimodal Sociosemiotics. Findings remarked how shared understandings about digital games can find their way into platforms and act as “cultural-technical gatekeepers”, supporting or hindering the engagement with game-making of those often perceived as outsiders to gaming culture. This gatekeeping happens when there are “creative dissonances” between, for example, personal preferences and platforms aligned to normative/mainstream genres. These dissonances, however, can end up fostering subversive designs, contravening gaming conventions and potentially challenging traditional gaming boundaries. This insight is relevant for understanding “cultural-technical constraints” and subversive/non-mainstream game-making, especially in relation to innovation and appropriation of game-making resources/strategies by non-mainstream groups.
Number: 2
Keywords: 1-Jeux vidéo; 1-TV; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Digital Disruption in South African Television News - Stos, Susan (Television in Africa in the Digital Age, 2021)
The term digital “disruption” conjures up negative connotations, with implications of disturbance, interference or interruption. Certainly, virtually every aspect of life has been affected by digitisation, but it has been pointed out that it is detrimental “only for those who chose to ignore it or try to ﬁght it” (“Digital Disruption: What Is It?” 2016, para 2). One case in point is the American company Kodak. Where it once dominated the ﬁlm and camera market for most of the twentieth century, the company recently ﬁled for bankruptcy. Kodak’s mistake was continually opposing the digitisation of the industry and failing to read the writing on the wall (“Digital Disruption: What Is It?” 2016). Digitisation is as much a reality of life in the newsroom as it is in the boardroom.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; Afrique du Sud (corpus analysé); Afrique du Sud (lieu de production du savoir); _Nettoyé

Chinese Television and Soft Power Communication in Australia - Li, Mei (Anthem Press, 2019)
Chinese Television and Soft Power Communication in Australia discusses China’s soft power communication approach and investigates information handling between China and its targeted audiences in the eyes of key influencers – intermediate elites (public diplomacy policy elites in particular) in China and Australia. It explores CGTN (with staff from several professional cultures) and conducts a systemic test of how successful/unsuccessful China’s soft power message projection is in terms of congruence between projected and received frames as a pivotal factor of its power status. The analysis is based on a case study of frames in the messaging on Chinese international TV about China’s Belt and Road Initiative and in the minds of Australian public diplomacy policy elites. The question raised is whether and how Australia is listening.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Océanie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; Australie (corpus analysé); Chine (corpus analysé); Chine (lieu de production du savoir); _Nettoyé

Making of Exile Culture: Iranian Television in Los Angeles - Naficy, Hamid (University of Minnesota Press, 1993)
Naficy explores the seemingly contradictory way in which immigrant media and cultural productions serve as the source both of resistance and opposition to the domination by host and home country's social values while simultaneously serving as vehicles for personal and cultural transformation and assimilation of those values.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice PANDC; Iran (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Representing Black Britain: Black and Asian Images on Television - Malik, Sarita (SAGE Publications, Limited, 2001)
'One of the most important books on race, representation and politics to come along in a decade' - Henry Giroux, Penn State University Representing Black Britain offers a critical history of Black and Asian representation on British television from the earliest days of broadcasting to the present day.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Arab Television Industries - Khalil, Joe; Kraidy, Marwan M. (BFI Publishing, 2009)
In recent years, Arab television has undergone a dramatic and profound transformation from terrestrial, government-owned, national channels to satellite, privately owned, transnational networks. The latter is the Arab television that matters today, economically, socially and politically. The resulting pan-Arab industry is vibrant, diverse, and fluid - very different, the authors of this major new study argue, from the prevailing view in the West, which focuses only on the al-Jazeera network. Based on a wealth of primary Arabic language sources, interviews with Arab television executives, and the authors' personal and professional experience with the industry, Arab Television Industries tells the story of that transformation, featuring compelling portraits of major players and institutions, and captures dominant trends in the industry. Readers learn how the transformation of Arab television came to be, the different kinds of channels, how programs are made and promoted, and how they are regulated. Throughout, the analysis focuses on the interaction of the television industry with Arab politics, business, societies and cultures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Créateur.rice PANDC; Qatar (lieu de production du savoir); _Nettoyé

Introduction: I See Black People - Smith-Shomade, Beretta E. (Watching While Black, 2012)
This project has been engaging my thoughts for nearly a decade. I was forced to actually address it while sitting in our temporary home in Ile-Ife, Nigeria, watching world satellite TV with virtually no Blacks on it. In Nigeria, I became acquainted with Paris-based Fashion TV, U.S.-based Style Network, and the Australian production McLeod’s Daughters. Outside of M-Net’s Africa Magic, a network dedicated to showing Nollywood productions primarily, television was anything but Black. This whitening of the televisual frame, even in Black Africa, made me begin to consider the dearth of knowledge circulating about Black television programming, even when abundance
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Cinema and Television in Singapore: Resistance in One Dimension - Tan, Kenneth (BRILL, 2008)
Through close readings of contemporary made-in-Singapore films (by Jack Neo, Eric Khoo, and Royston Tan) and television programs (Singapore Idol, sitcoms, and dramas), this book analyzes the prospects of resistance in an advanced capitalist-industrial society with "global city" aspirations.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Créateur.rice PANDC; Singapour (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

African Television in the Age of Globalization, Digitization, and Media Convergence - Eko, Lyombe (The Routledge Companion to Global Television, 2019)
African television is at the crossroads. This chapter surveys, describes, analyzes and explains the major changes that have taken place in the African television landscape since the 1990s. It focuses on three major developments that have marked the African television landscape: (1) liberalization of the television space to keep abreast of international developments, and the tension between entrenched governmental public broadcasting systems and newly licensed “independent” TV stations, (2) the process and impact of the analogue to digital TV switchover shepherded by the International Telecommunications Union, and (3) the diffusion of Chinese electronic technology, television, and film content on the African television market as part of the Asian giant’s “soft power” diplomacy and State capitalism. African television is constrained by political regimes that restrict freedom of expression, and regulatory agencies that preside over systems in which the law takes precedence over rights.
Num Pages: 15
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (lieu de production du savoir)

Screening Right-Wing Populism in “New Turkey”: Neo-Ottomanism, Historical Dramas, and the Case of Payitaht Abdulhamid - Bulut, Ergin; İleri, Nurçin (The Routledge Companion to Global Television, 2019)
This chapter examines the intersection of popular culture and populism in Turkey by focusing on the TV show Payitaht Abdulhamid. Our motivation to analyze the recent TV series Payitaht Abdulhamid stems from our interest in the instrumental mobilization of popular culture for the Turkish government’s dual desire to both establish cultural hegemony and consolidate its populist style of government. Our analysis reveals that television, especially in the Global South, still plays a central role in governments’ desire to reconstruct history and establish cultural hegemony. This is particularly important as Turkey is going through a crisis of hegemony since the public is completely divided in its support for the government. Within the context of this hegemonic crisis, televised popular culture is vital, perhaps more than ever. Specifically, the show reduces a complicated history into easily understandable dichotomies and projects them on to contemporary politics in order to consolidate support for the government. Through televised popular culture, the government mobilizes history for purposes of cultural hegemony and populist politics flavored with nationalist, Islamist, and anti-Western motifs. Ultimately, the TV show presents yet another moment for understanding the mediated nature of 21st-century politics outside Western contexts.
Num Pages: 12
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Venezuela : Fiction in the Dark - Alvarado, Morella; Torrealba, Luisa (Obitel 2020: Melodrama in Times of Streaming, 2020)
During 2019, various situations once again showed the deep crisis in the country. Audiovisual production continued, albeit with figures that account for a declining industry. Four productions were released: a first was made by the state channel (TVe), a second by a local independent producer (Oduver Cubillán and BGcreativos), the third was produced by the private channel (RCTV) and broadcast by the subscription channel IVC Networks, and the fourth was also produced by RCTV. While the first two productions did not exceed the 35-episode figure, the third and fourth had 73 episodes. On March 7, there was the biggest blackout in the country’s history. For more than a week, 95% of the territory was paralyzed by a lack of electricity. The action was classified by the government as an electric sabotage. The darkness that covered the country also subsumed serial fiction.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Venezuela (corpus analysé); Venezuela (lieu de production du savoir); _Nettoyé

Uruguay: Ibero-American Fiction Loses Ground to Entertainment - Sánchez Vilela, Rosario; Gadea, Lucia (Obitel 2020: Melodrama in Times of Streaming, 2020)
A look at the screens of Uruguay’s open television in prime time will give the viewer a very reduced offer: after a television newscast that exceeds two hours long, there are only contest pro- grams, national or imported ones. It is possible that in the afternoon and at night the viewer finds a telenovela, almost always Turkish one. This is a very different panorama from the Uruguayan televi- sion history. Ibero-American fiction is in decline on open television, while its offer on VoD expands. In this chapter we will try to consider the various aspects of this landscape. Melodrama is on both options, open television and streaming, on a broad thematic spectrum, even in productions that are not usually classified as such. In the absence of national fiction in the period, at the end of the chapter we will study the melodrama in prison fiction, particularly in the case of El Marginal.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Uruguay (corpus analysé); Uruguay (lieu de production du savoir); _Nettoyé

Pratiques professionnelles en arts visuels issues de l'autochtonie et de la diversité à Montréal - Uzel, Jean-Philippe; Conseil des arts de Montréal (2017)
Rapport commandé par le Conseil des arts de Montréal
OCLC: 1081308169
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Game Devs & Others: Tales from the Margins - DePass, Tanya (CRC Press, 2018)
Game Devs & Others: Tales from the Margins tell the true stories of life in the industry by people of color, LGBTQIA and other marginalized identities. This collection of essays give people a chance to tell their stories and to let others know what life on the other side of the screen is like when you’re not part of the supposed “majority”. Key Features This book is perfect for anyone interested in getting into the games industry who feels they have a marginalized identity For those who wish to better diversify their studio or workplace who may or may not have access to individuals that could or would share their stories about the industry Includes initiatives aimed at diversifying the industry that have a positive or negative impact on the ongoing discussions Coverage of ajor news items about diversity, conferences aimed at or having diversity at its core of content and mission are discussed Included essays are written with as little game dev specific jargon as possible, makeing it accessible to people outside the industry as well as those in the scene but that may not have all the insider lingo
Google-Books-ID: Gv5cDwAAQBAJ
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Interview with Deyfou-lah Sani Bah-Traore on the Togolese Game Origin - the Rise of Dzitri - Kienzl, Lisa; Bah-Traore, Deyfou-lah Sani (Gamevironments, 2019)
In the Togelese game Origin - the Rise of Dzitri that was developed in Lome, the character Edoh takes you on a journey to historic places in the city to revive the spirit of Dzitri. Deyfou-lah Sani Bah-Traore, programmer and game developer, spoke with Lisa Kienzl about his and his Teammate s work on Origin - the Rise of Dzitri
Accepted: 2020-03-25T23:30:30Z
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Interview with Mira Wardhaningsih from StoryTale Studios on the Indonesian Horror Game Pamali - Trattner, Kathrin; Wardhaningsih, Mira (Gamevironments, 2019)
An interview by Kathrin Trattner with Mira Wardhaningsih, Cultural Content Director from StoryTale Studios about the game Pamali
Accepted: 2020-03-25T23:30:30Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Interview With Ryan Sumo, Lead Artist/Business Developer At Squeaky Wheel Studio - Radde-Antweiler, Kerstin; Sumo, Ryan (Gamevironments, 2018)
Interview with Ryan Sumo, Lead Artist/Business Developer at Squeaky Wheel Studio
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview With Ben Joseph P. Banta, Founder Of Ranida Games - Radde-Antweiler, Kerstin; Banta, Ben Joseph P. (Gamevironments, 2018)
Interview With Ben Joseph P. Banta, Founder Of Ranida Games
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview With The Creator Of Boo! Dead Ka! Game - Radde-Antweiler, Kerstin; Prieto, Kurt (Gamevironments, 2018)
Interview with With Kurt Prieto, Games Designer Of Boo! Dead Ka! Game
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Zainuddeen Fahadh, Founder of Ogre Head Studio - Zeiler, Xenia; Zainuddeen, Fahadh (Gamevironments, 2018)
Interview with Zainuddeen Fahadh, Founder of Ogre Head Studio, Hyderabad, India
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Avinash Kumar, Creative Director & Co-Founder, Quicksand Design Studio - Zeiler, Xenia; Kumar, Avinash (Gamevironments, 2018)
Interview with Avinash Kumar, Creative Director & Co-Founder, Quicksand Design Studio, India.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Avichal Singh, Founder and Game Designer of Nodding Heads Games - Zeiler, Xenia; Singh, Avichal (Gamevironments, 2018)
Interview with Avichal Singh, Founder and Game Designer of Nodding Heads Games, Pune, India.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Satyajit Chakraborty, Founder of Flying Robot Studios, Kolkata, India - Zeiler, Xenia; Chakraborty, Satyajit (Gamevironments, 2018)
Accepted: 2020-03-25T23:30:08Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Shailesh Prabhu, Indian Game Designer - Prabhu, Shailesh (Game Studies, 2016)
Interview with the Indian Game Designer Shailesh Prabhu about his game Sky Sutra.
Accepted: 2020-03-25T23:29:20Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Créateur.rice PANDC; _Nettoyé

Featuring Females: Feminist Analyses of Media - Cole, Ellen; Daniel, Jessica Henderson (American Psychological Association, 2005)
"Featuring Females analyzes the portrayals of women in a variety of outlets, including reality television shows, films, print and electronic news programming, magazines, video games, and commercial advertising. A highly esteemed group of scholars and researchers provides informed, original psychological study, and their thought-provoking findings address the ways in which aging, race/ethnicity, body image, gender roles, sexual orientation and relationships, and violence are treated in the media. Featuring Females is a diverse volume, exploring images and characterizations of women young and old and inspiring discussion of the effects that these representations have on girls, women, and society at large"–
OCLC: 57754311
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé; _À analyser; _À vérifier-Cinéma; _À vérifier-Télé

First Person Encounters #5: Abhi, creator of Venba - Game Studies India Adda
Venba is a narrative cooking game, where you play as an Indian mom, who immigrates to Canada with her family in the 1980s. Players will cook various dishes and restore lost recipes, hold branching conversations and explore in this story about family, love, loss and more. More on Steam: https://store.steampowered.com/app/14.... Developer, Abhi, gives Game Studies India an exclusive preview talking about identity, nostalgia, memory and of course, food. In conversation with Poonam Chowdhury and Souvik Mukherjee.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

First-Person Encounters #4: Poornima Seetharaman - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we talk with Poornima Seetharaman. She is the first Indian to be inducted in the Women in Games (WIGJ) Hall of Fame and is also the lead game designer at Zynga. Hear as we talk about her foray in the world of gaming.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

First-Person Encounters #2: Satyajit Chakaborty - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our second podcast where we interview Satyajit Chakraborty, a game developer, game designer and researcher. He also founded Flying Robots Studios in 2012 and has made various unique games. Here he talks about his first experiences with gaming in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Palgrave Macmillan, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Section: xi, 279 p. : ill. ; 23 cm.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

A Critical Interpretation of a New “Creative Industry” in Turkey: Game Studios and the Production of a Value Chain - Binark, Mutlu; Bayraktutan, Günseli (Computer Games and New Media Cultures: a Handbook of Digital Games Studies, 2012)
In this chapter, the creation of a value chain during the process of digital games development in Turkey is discussed using a critical political economy approach. This study claims to be the first of its kind that intends to examine the topography of the digital game industry in Turkey and gives a brief history and describes the present status of digital games production in Turkey. All the components of a value chain, namely, the industrial structure and development process, publishing and licensing, distribution and marketing structure, labor force, legal regulations, and governmental policies will be considered in that order to map out the present topography of the industry. The final part of the study will deal with possible solutions for further development in the industry. At this point, the study stresses the fact that all components of the value chain must be performed uninterrupted if the actors in Turkey’s digital game industry desire to position themselves as “producers” in global or local markets.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé